Informational Aspects of the Haptic Stimulation by the Light for Correction of the Human’ State - Bachynskyy, M.V.; Yavorskyy, B.I. (Кибернетика и вычислительная техника, 2018)
The purpose of the article is to specify the informational aspects of low intensity, haptic stimulation by the light, which is essential for correction of the functional state of an organism of the human being, who works in extreme conditions, to develop and study such methods and systems. Methods. Analyses of requirements, functions and systems for designing synthesis of information technologies and the control biotechnical system of correction of the functional state of an organism of the human, who works in extreme conditions. The theoretical and experimental dependences between the stimulation energy of light emission diode (LED) and the energy are transferred through the layered bio media design. Mathematical modelling and computational simulation. Comparison of these real and model data. Results. The base aspects requirements, functions and systems for designing synthesis of information technologies and the control biotechnical system of correction of the functional state of an organism of the human, who works in extreme conditions, low intensity, haptic stimulation by the light are defined. The methods for determining of intensity I₀ of light emission diode, recursive expression Im = СmIm-1, m = 1,M and formula for coefficient Cm , where M — quantity of bio media layers were developed. The bridges, which connects Maxwell's phenomenological theory with the atomistic theory of matter and optics, were used. Computer simulation studies have confirmed the specification of requirements, functional and structural schemas of biotechnical system. Розглянуто аспекти інформаційних процесів в медико-біологичних системах організму людини в екстремальних умовах її діяльності та розвинуто теорію медичних інформаційних систем з урахуванням стану і тенденцій конвергенції суспільства, екосистеми і технологій. Запропоновано специфікацію інформаційних аспектів гаптичної стимуляції світлом для корекції функціонального стану організму та розвитку й дослідження вимог до функцій, методів та структур відповідних біотехнічних систем. Наведено функціональну схему біотехнічної системи та результати аналізу зміни інтенсивності світла при поширенні його у шаруватому біо середовищі від світлодіодного джерела стимуляції. Цель статьи — уточнить информационные аспекты низкой интенсивности тактильной стимуляции светом, которая необходима для коррекции функционального состояния организма человека, работающего в экстремальных условиях, и дальнейшего развития и исследования таких методов и систем. Методы. Анализ требований, функций и систем для проектирования синтеза информационных технологий и контрольной биотехнической системы коррекции функционального состояния организма человека, работающего в экстремальных условиях. Теоретические и экспериментальные зависимости между энергией стимуляции светоизлучающего диода и энергией передаются через слоистую структуру биоресурсов. Математическое моделирование и компьютерное моделирование. Сравнение этих реальных и модельных данных. Результаты. Базовые аспекты требований, функций и систем для разработки, синтеза информационных технологий и управляющих биотехнических систем коррекции функционального состояния организма человека, работающего в экстремальных условиях, с низкой интенсивностью тактильной стимуляции светом. Получены методы определения интенсивности I0 излучения светодиода, рекурсивные выражения Im = СmIm-1, m = 1,M и формулы для коэффициента Cm, где M — количество слоев биосреды. Использована связь феноменологической теории Максвелла с атомистической теорией материи и оптикой. Исследования компьютерного моделирования подтвердили результат спецификации требований, функциональных и структурных схем биотехнической системы.